Short-chain fatty acids in diseases - Zhang, Dan; Jian, Yong-Ping; Zhang, Yu-Ning; Li, Yao; Gu, Li-Ting; Sun, Hui-Hui; Liu, Ming-Di; Zhou, Hong-Lan; Wang, Yi-Shu; Xu, Zhi-Xiang (Cell communication and signaling, 2023)
Short-chain fatty acids (SCFAs) are the main metabolites produced by bacterial fermentation of dietary fibre in the gastrointestinal tract. The absorption of SCFAs is mediated by substrate transporters, such as monocarboxylate transporter 1 and sodium-coupled monocarboxylate transporter 1, which promote cellular metabolism. An increasing number of studies have implicated metabolites produced by microorganisms as crucial executors of diet-based microbial influence on the host. SCFAs are important fuels for intestinal epithelial cells (IECs) and represent a major carbon flux from the diet, that is decomposed by the gut microbiota. SCFAs play a vital role in multiple molecular biological processes, such as promoting the secretion of glucagon-like peptide-1 by IECs to inhibit the elevation of blood glucose, increasing the expression of G protein-coupled receptors such as GPR41 and GPR43, and inhibiting histone deacetylases, which participate in the regulation of the proliferation, differentiation, and function of IECs. SCFAs affect intestinal motility, barrier function, and host metabolism. Furthermore, SCFAs play important regulatory roles in local, intermediate, and peripheral metabolisms. Acetate, propionate, and butyrate are the major SCFAs, they are involved in the regulation of immunity, apoptosis, inflammation, and lipid metabolism. Herein, we review the diverse functional roles of this major class of bacterial metabolites and reflect on their ability to affect intestine, metabolic, and other diseases. 1p-zsPMrd9abnhs73Aes5_ Video Abstract